Efficacy and Safety of Ibrutinib in Central Nervous System Lymphoma: A PRISMA-Compliant Single-Arm Meta-Analysis - Lv, Liwei; Sun, Xuefei; Wu, Yuchen; Cui, Qu; Chen, Yuedan; Liu, Yuanbo (Frontiers in Oncology, 2021)
Background: Central nervous system lymphoma (CNSL) is an aggressive lymphoma. Studies investigating primary CNSL determined that the Bruton tyrosine kinase (BTK) played an important role in pathogenesis. Ibrutinib, an oral BTK inhibitor, is a new treatment strategy for CNSL. The purpose of this meta-analysis was to clarify the effectiveness and safety of ibrutinib in the treatment of CNSL. Methods: A systematic search of PubMed, Embase, Cochrane library, Wanfang Data Knowledge Service Platform, and China National Knowledge Infrastructure databases was conducted through to 31 October 2019. Studies involving patients with CNSL who received ibrutinib that reported the overall response (OR), complete remission (CR), and partial response (PR) were included. The random-effects or fixed-effects model with double arcsine transformation was used for the pooled rates and 95% confidence intervals (CI) were determined for all outcomes. Results: Eight studies including 162 patients were identified and included in the meta-analysis. The pooled OR rate after treatment with ibrutinib was 69% (95% CI, 61–79%, I2 = 47.57%, p = 0.06), while the pooled CR and PR was 52% (95% CI, 35–68%, I2 = 74.95%, p = 0.00) and 17% (95% CI, 7–30%, I2 = 67.85%, p = 0.00), respectively. Common adverse events above grade 3 included cytopenia and infections. Conclusions: The ibrutinib-containing therapy was well tolerated and offered incremental benefit to patients with CNSL. However, randomized-controlled studies that directly compare efficacy and adverse events of ibrutinib are still needed. Registration: This meta-analysis was registered in the international prospective register of systematic reviews (PROSPERO) (CRD42020218974).